Single‐cell polyadenylation site mapping reveals 3′ isoform choice variability. Issue 6 (3rd June 2015) - Velten, Lars; Anders, Simon; Pekowska, Aleksandra; Järvelin, Aino I; Huber, Wolfgang; Pelechano, Vicent; Steinmetz, Lars M
Abstract Cell‐to‐cell variability in gene expression is important for many processes in biology, including embryonic development and stem cell homeostasis. While heterogeneity of gene expression levels has been extensively studied, less attention has been paid to mRNA polyadenylation isoform choice. 3′ untranslated regions regulate mRNA fate, and their choice is tightly controlled during development, but how 3′ isoform usage varies within genetically and developmentally homogeneous cell populations has not been explored. Here, we perform genome‐wide quantification of polyadenylation site usage in single mouse embryonic and neural stem cells using a novel single‐cell transcriptomic method, BATSeq. By applying BATBayes, a statistical framework for analyzing single‐cell isoform data, we find that while the developmental state of the cell globally determines isoform usage, single cells from the same state differ in the choice of isoforms. Notably this variation exceeds random selection with equal preference in all cells, a finding that was confirmed by RNA FISH data. Variability in 3′ isoform choice has potential implications on functional cell‐to‐cell heterogeneity as well as utility in resolving cell populations.